Patients with anti-SAE+ dermatomyositis display refractory and difficult-to-treat skin manifestations: case series from two Italian cohorts and review of literature - Depascale, Roberto; Ghirardello, Anna; Zanatta, Elisabetta; Franco, Chiara; Bracalenti, Marisol; Pettorossi, Federico; Gatto, Mariele; Treppo, Elena; Moccaldi, Beatrice; Zen, Margherita; Piaserico, Stefano; Ciolfi, Christian; et al. (Frontiers in Immunology, 2025)
AimWe aimed to describe the clinical and serological characteristics of anti-small ubiquitin-like modifier-activating enzyme (SAE)-positive cases from a multicentric cohort of patients affected with idiopathic inflammatory myopathies (IIMs).MethodsAnti-SAE antibody-positive patients (determined by line immunoassay) from a prospective cohort of patients with IIM were retrospectively evaluated. We considered features at disease onset and during follow-up. Muscular involvement was evaluated by the Manual Muscle Test-8, creatine phosphokinase (CK) levels, and/or magnetic resonance imaging; interstitial lung disease (ILD) was evaluated by high-resolution computed tomography; and skin and joint involvement was evaluated by clinical judgment. The therapeutic approach was also reported in all patients, and a literature review was also provided.ResultsOut of 170 patients with IIM, 10 (5.9%) were anti-SAE positive, all classified as having dermatomyositis; therefore, among 80 patients with dermatomyositis, the prevalence of anti-SAE antibodies was 12.5%. The female-to-male ratio was 9:1. The median time from onset of symptoms to diagnosis was 1 year (range 0–2 years), and the mean age at onset of symptoms was 55.5 years (range 34–77 years). All patients had skin manifestations, including photosensitive rash, heliotrope rash, and Gottron’s sign and/or papules (one with ulcerations). Refractory features requiring multiple lines of immunosuppressants were observed in 60% of cases. Four patients had arthritis and/or inflammatory arthralgia; four had muscular involvement, usually mild; and none had ILD. One patient had a history of malignancy. All patients were treated with glucocorticoids and received different immunosuppressants, including cyclophosphamide.ConclusionsAll patients with anti-SAE antibody positivity were classified as having dermatomyositis, with severe and refractory skin manifestations in most cases. One case of malignancy was described; therefore, cancer screening should be warranted in all anti-SAE patients.